2006
DOI: 10.1016/j.apacoust.2005.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Parameter study of sound propagation between city canyons with a coupled FDTD-PE model

Abstract: A parameter study is performed for the case of two-dimensional sound propagation from a (source) city canyon to a nearby, identical (receiver) city canyon. Focus was on sound pressure levels, relative to the free field, in the shielded canyon. An accurate and efficient coupled FDTD-PE model was applied, exploiting symmetry of the source and receiver canyon. With the proposed calculation method, simulations were necessary in only half the sound propagation domain. The shielding in the receiver canyon in case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 24 publications
2
76
0
1
Order By: Relevance
“…Consequently, this concept has become part of the noise policy in a number of European cities [114]. Therefore, potentially quiet areas, like urban courtyards, have been studied in detail [115][116][117][118][119][120][121][122]. Although courtyards are often strongly shielded from direct exposure to road traffic noise, many of such places were found to exhibit noise levels that are too high to function as quiet areas [123].…”
Section: Building Envelope Greeningmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, this concept has become part of the noise policy in a number of European cities [114]. Therefore, potentially quiet areas, like urban courtyards, have been studied in detail [115][116][117][118][119][120][121][122]. Although courtyards are often strongly shielded from direct exposure to road traffic noise, many of such places were found to exhibit noise levels that are too high to function as quiet areas [123].…”
Section: Building Envelope Greeningmentioning
confidence: 99%
“…Therefore, mitigation measures to reduce noise levels in urban courtyards are required to fully benefit from access to quietness. The potential of various measures has already been explored [115,119,124,125]. It was found that both façade and roof treatments can contribute significantly to the mitigation of noise from road traffic outside the courtyard.…”
Section: Building Envelope Greeningmentioning
confidence: 99%
See 2 more Smart Citations
“…1 a). The latter is responsible of building up a diffuse sound field in the canyons, which could influence the effectiveness of treatments [38][42]. All buildings have similar façades.…”
mentioning
confidence: 99%